Crucial conversations : tools for talking when stakes are high - Patterson, Kerry, 1946- (New York : McGraw-Hill, 2002)
A seven-step approach to handling difficult conversations with confidence and skill. "Crucial" conversations are interpersonal exchanges at work or at home that we dread having but know we cannot avoid. How do you say what needs to be said while avoiding an argument with a boss, child, or relationship partner? This book offers readers a proven seven-point strategy for achieving their goals in all those emotionally, psychologically, or legally charged situations that can arise in their professional and personal lives. Based on the authors' DialogueSmart training seminars, the techniques are geared toward getting people to lower their defenses, creating mutual respect and understanding, increasing emotional safety, and encouraging freedom of expression. Among other things, readers also learn about the four main factors that characterize crucial conversations, and they get a six-minute mastery technique that prepares them to work through any high-impact situation with confidence.--From publisher description
What's a crucial conversation? -- Mastering crucial conversations -- Start with heart -- Learn to look -- Make it safe -- Master my stories -- STATE my path -- Explore others' paths -- Move to action -- Putting it all together -- Yeah, but -- Change your life
leisure reading
Includes bibliographical references (p. 229) and index
Keywords: Interpersonal communication; Interpersonal relations